The Relationships Between Reading Speed, Phonological Awareness and Word Recognition Skills of Primary School Students - Gökmen, Ayşe Dilek Yekeler (Bartin University, 2026)
In this study, it was aimed to determine the reading speed, phonological awareness and word recognition levels of primary school students at the beginning of the process of learning to read, the relationships between these variables and the role of reading speed in the longitudinal development observed in the first and second grades. In order to examine the reading skills of primary school students according to various variables, predictive design, one of the relational research types, was used in the study. The study group consisted of 32 students. In the analysis of the research data, descriptive statistics of the variables were followed by relational analysis. The results of the study showed that the second grade reading rate of the students was higher than the first grade reading rate, and that the first grade reading rate and word recognition skill variables were significant predictors of the second grade reading rate. These two variables together explain the majority of the change in second grade reading speed. This situation was interpreted as second grade students' reading skills continued to improve, they recognized words more easily, but the contribution of phonological awareness to the process decreased unlike the beginning of the first reading process.

Bu araştırmada okumayı öğrenme sürecinin başındaki ilkokul öğrencilerinin okuma hızları ile ses bilgisel farkındalık ve kelime tanıma düzeylerinin nasıl olduğu, bu değişkenler arasındaki ilişkiler ile okuma hızının birinci ve ikinci sınıfta gözlenen boylamsal gelişimindeki rolünün belirlenmesi amaçlanmıştır. İlkokul öğrencilerinin okuma becerilerinin çeşitli değişkenlere göre incelenmesi amacıyla araştırmada ilişkisel araştırma türlerinden yordayıcı desen kullanılmıştır. Araştırmanın çalışma grubunu 32 öğrenci oluşturmuştur. Araştırma verilerinin analizinde değişkenlere ait tanımlayıcı istatistiklerin ardından ilişkisel analizlere başvurulmuştur. Araştırma sonuçları öğrencilerin ikinci sınıf okuma hızlarının, birinci sınıftan daha yüksek olduğunu; yordayıcı değişkenlerden birinci sınıf okuma hızı ve kelime tanıma becerisi değişkenlerinin, ikinci sınıf okuma hızı üzerinde anlamlı yordayıcı olduğunu göstermiştir. Adı geçen bu iki değişken birlikte ikinci sınıf okuma hızındaki değişimin büyük çoğunluğunu açıklamaktadır. Bu durum ikinci sınıf öğrencileri için okuma becerilerinin gelişmeye devam ettiği, sözcükleri daha kolay tanındıkları fakat ses bilgisel farkındalığın ilk okuma sürecinin başından farklı olarak sürece katkısının azaldığı şeklinde yorumlanmıştır
İlkokul Öğrencilerinin Okuma Hızları ile Ses Bilgisi Farkındalık ve Kelime Tanıma Becerileri Arasındaki İlişkiler
Keywords: Primary Education; İlköğretim